Numerical Study of the Effect of Grid Number and Viscous Model on Fin and Tube Heat Exchanger Performance - MUHAMAD SAFI'I; NAZARUDDIN SINAGA; EFLITA YOHANA; YAFID EFFENDI; AKHMAD IRFAN; SUHERI SUHERI; ROUF MUHAMMAD; AGUNG NUGROHO; CANDRA WAHYU SPORTYAWAN (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2026)
The fin and tube heat exchanger (FTHE) has attracted attention among technicians and researchers because of its performance. This research was conducted to determine the effect of variations in the number of grids and viscous models on FTHE on its thermal performance using the Fluent application in the Computational Fluid Dynamics computer program, which was varied against the number of grids and viscous models in various variations of fluid flow speed with a constant heat flux of 100 W. The best results of this research were obtained with the variation of the longitudinal pitch ratio of 14.5 mm with a heat transfer coefficient value of 97.24 W/m2K, while the ratio of the transverse pitch direction of 11.7 mm with a heat transfer coefficient value of 107.82 W/m2K. The best results of this research were obtained at variations in the number of grids of 358456 in variations of the viscous k-w Standard model with an average FTHE temperature value of 21.35 oC and a maximum heat transfer coefficient value of 101.74 W/m2K. These results confirm that the variation of the number of grids of 358456 in the variation of the viscous k-w Standard model allows the numerical study model to be recommended and used for practical applications on machine devices, and can be applied directly in the field. Keywords: Fin and Tube Heat Exchanger (FTHE), Longitudinal Pitch, Transversal Pitch, Performa.